Maintenance of Elective Patient Care at Berlin University Children's Hospital During the COVID-19 Pandemic - Terliesner, Nicolas; Rosen, Alexander; Kaindl, Angela M.; Reuter, Uwe; Lippold, Kai; Mall, Marcus A.; Bernuth, Horst von; Gratopp, Alexander (Frontiers in Pediatrics, 2021)
Background: In Germany, so far the COVID-19 pandemic evolved in two distinct waves, the first beginning in February and the second in July 2020. The Berlin University Children’s Hospital at Charité (BCH) had to ensure treatment for children not infected and infected with SARS-CoV-2. Prevention of nosocomial SARS-CoV-2 infection of patients and staff was a paramount goal. Pediatric hospitals worldwide discontinued elective treatments and established a centralized admission process. Methods: The response of BCH to the pandemic adapted to emerging evidence. This resulted in centralized admission via one ward exclusively dedicated to children with unclear SARS-CoV-2 status and discontinuation of elective treatment during the first wave, but maintenance of elective care and decentralized admissions during the second wave. We report numbers of patients treated and of nosocomial SARS-CoV-2 infections during the two waves of the pandemic. Results: During the first wave, weekly numbers of inpatient and outpatient cases declined by 37 % (p < 0.001) and 29 % (p = 0.003), respectively. During the second wave, however, inpatient case numbers were 7 % higher (p = 0.06) and outpatient case numbers only 6 % lower (p = 0.25), compared to the previous year. Only a minority of inpatients were tested positive for SARS-CoV-2 by RT-PCR (0.47 % during the first, 0.63 % during the second wave). No nosocomial infection of pediatric patients by SARS-CoV-2 occurred. Conclusion: In contrast to centralized admission via a ward exclusively dedicated to children with unclear SARS-CoV-2 status and discontinuation of elective treatments, maintenance of elective care and decentralized admission allowed the almost normal use of hospital resources, yet without increased risk of nosocomial infections with SARS-CoV-2. By this approach unwanted sequelae of withheld specialized pediatric non-emergency treatment to child and adolescent health may be avoided.